Transient unilateral brachial plexopathy and partial Horner's syndrome following spinal anesthesia for cesarean section - Jonathan A Anson; Patrick M McQuillan (Wolters Kluwer Medknow Publications, 2014)
A healthy 21-year-old primigravida presented for elective cesarean section. At 45 min after intrathecal (IT) injection of bupivacaine, morphine and fentanyl she developed dysphagia, right sided facial droop, ptosis and ulnar nerve weakness. This constellation of signs and symptoms resolved 2 h later. Based on the time course and laterality of her symptoms, as well as the pharmacologic properties of spinal opioids, we believe her symptoms can be attributed to the IT administration of fentanyl.